Characterization of polylactic acid/organoclay nanocomposites - Ali, Fathilah; Azmi, Azlin Suhaida; Anuar, Hazleen; Jamaluddin, Jamarosliza (Springer, Singapore, 2020)
Polylactic acid (PLA) is a biodegradable polymer that can be substituted in usage of conventional non-degradable polymers. The strength of the PLA can be enhanced by incorporating clay. In this research, PLA was mixed with organoclay (Cloisite 30B, C30B) using Haake internal mixer. The X-ray diffraction (XRD) patterns and transmission electron microscopy (TEM) images showed that PLA chains were intercalated into the layers of the organoclay. The thermal properties showed a slight decrease in the glass transition temperature of PLA, and similar trend was observed in Tan delta. The nanocomposites exhibited higher storage modulus than the matrix. The PLA/C30B nanocomposites exhibited increment in modulus of PLA by using organoclay, in which it is suitable to replace non-degradablematerials.